2023
DOI: 10.1021/acscentsci.2c01394
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Pathways of CdTeSe Magic-Size Cluster Isomerization Induced by Surface Ligands at Room Temperature

Abstract: The field of isomerization reactions for colloidal semiconductor magic-size clusters (MSCs) remains largely unexplored. Here, we show that MSCs isomerize via two fundamental pathways that are regulated by the acidity and amount of an incoming ligand, with CdTeSe as the model system. When MSC-399 isomerizes to MSC-422 at room temperature, the peak red-shift from 399 to 422 nm is continuous (pathway 1) and/or stepwise (pathway 2) as monitored in situ and in real time by optical absorption spectroscopy. We propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 53 publications
2
27
0
Order By: Relevance
“…The model of the PC‐assisted transformation (Scheme S2) explains well the experimental observation that MSCs display stepwise shifts of optical absorption and emission (Figure S1B). Furthermore, that the stepwise shifts are associated with PC‐assisted transformation is supported further by our recent observation of the continuous shift of the absorption spectra when CdTe MSC‐448 transforms to CdTe MSC‐488, [18, 19] and when CdTeSe MSC‐399 transforms to CdTeSe MSC‐422 (Figure S1C) [20] . These findings indicate that when a mother cluster transforms to a daughter cluster, the spectral shift is continuous.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…The model of the PC‐assisted transformation (Scheme S2) explains well the experimental observation that MSCs display stepwise shifts of optical absorption and emission (Figure S1B). Furthermore, that the stepwise shifts are associated with PC‐assisted transformation is supported further by our recent observation of the continuous shift of the absorption spectra when CdTe MSC‐448 transforms to CdTe MSC‐488, [18, 19] and when CdTeSe MSC‐399 transforms to CdTeSe MSC‐422 (Figure S1C) [20] . These findings indicate that when a mother cluster transforms to a daughter cluster, the spectral shift is continuous.…”
Section: Introductionsupporting
confidence: 73%
“…Furthermore, that the stepwise shifts are associated with PC-assisted transformation is supported further by our recent observation of the continuous shift of the absorption spectra when CdTe MSC-448 transforms to CdTe MSC-488, [18,19] and when CdTeSe MSC-399 transforms to CdTeSe MSC-422 (Figure S1C). [20] These findings indicate that when a mother cluster transforms to a daughter cluster, the spectral shift is continuous. Such an uninterrupted pattern is similar to that observed when QDs grow in size in a reaction.…”
Section: Introductionmentioning
confidence: 92%
“…On this basis, the as-obtained (CdS) 13 MSCs could act as a single precursor to form colloidal CdS nanoplatelets with a wurtzite structure. 49 In addition, Yu et al 50 demonstrated for the first time how colloidal semiconductor MSCs undergo isomerization at low temperatures under external chemical stimuli, namely, MSC-399 to MSC-422. Notably, ion exchange makes it possible for as-obtained MSCs to transform into their counterparts, indicating that new MSCs can be synthesized via a template-based approach (see Fig.…”
Section: Synthesis and Growth Mechanism Of Typical Ii–vi Mscsmentioning
confidence: 99%
“…It has been demonstrated that each MSC has its counterpart precursor compound (PC), where the former exhibits a characteristic sharp absorption signal and the latter is nonabsorbing. A MSC and its counterpart PC are a pair of quasi-isomers with similar chemical compositions for the inorganic core but different configurations. For example, a CdS MSC and its counterpart PC exhibit similar m / z values corresponding to the inorganic core in the matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectra . The metal (M) chalcogenide (E) PCs form in the induction period of a reaction prior to the nucleation and growth of ME quantum dots (QDs) via the self-assembling of M and E precursors followed by the formation of M-E covalent bonds inside each assembly. , The resulting PCs then transform to their counterpart MSCs upon incubation , or dispersing , at room temperature. It is noteworthy that the reversible transformations between ME PCs and their counterpart MSCs are quite similar to the reversible disorder–order transitions during the nucleation of atomic crystals .…”
Section: Introductionmentioning
confidence: 99%